Government Response in Addressing Social Issues through Direct Engagement: Best Practices from Singapore - Simbolon, Claudia Herlina Putri Sanda Nauli; Azijah, Dewi Noor; Aryani, Lina (Jurnal Studi Ilmu Pemerintahan, 2023)
This research aims to provide important guidance for the Indonesian Government in responding to pressing social issues. With a primary focus on delineating the level of responsiveness exhibited by the Singapore Government towards such issues, this research utilizes a methodological framework that includes qualitative content analysis and a critical discourse approach. This approach is crucial in understanding the nuanced aspects of responsiveness. The results of this study confirm that the Singapore Government demonstrates a high level of responsiveness, characterized by transparency and a relaxed approach to community engagement, a very important component in addressing social issues. This research provides invaluable insights for the GoI and catalyzes it to formulate more productive strategies to address social challenges. The implications of these findings resonate across the socio-political landscape, strengthening the interaction between government and society. This, in turn, paves the way for the implementation of policies that are inherently more inclusive, ultimately leading to improved quality of life.